2012
DOI: 10.1143/jjap.51.090129
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Vein Endothelial Cell Interaction with Fluorine-Incorporated Amorphous Carbon Films

Abstract: A major clinical concern in coronary intervention for cardiovascular disease is late stent thrombosis after the implantation of drug eluting stents (DES). DES widely used in clinical settings currently utilize polymer coatings, which can induce persistent arterial wall inflammation and delayed vascular healing, resulting in impaired endothelialization. We examined the viability of human umbilical vein endothelial cells (HUVECs) for fluorine-incorporated amorphous carbon (a-C:H:F) coatings, which are known to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Yoshimoto et al examined the viability of human umbilical vein endothelial cells (HUVECs) for fluorine-incorporated DLC (F-DLC) coatings [77]. F-DLC was synthesized on tissue-culture dishes using radio frequency plasma enhanced chemical vapor deposition by varying the ratio of hexafluoroethane and acetylene.…”
Section: Plasma Applications To Polymers In the Tissue Engineeringmentioning
confidence: 99%
“…Yoshimoto et al examined the viability of human umbilical vein endothelial cells (HUVECs) for fluorine-incorporated DLC (F-DLC) coatings [77]. F-DLC was synthesized on tissue-culture dishes using radio frequency plasma enhanced chemical vapor deposition by varying the ratio of hexafluoroethane and acetylene.…”
Section: Plasma Applications To Polymers In the Tissue Engineeringmentioning
confidence: 99%
“…However, low adhesion force makes it impossible to grow highly organized fibrin clots. a-C:H:F coatings were reported to possess great potential as coatings that can prevent thrombus formation on medical devices that come into contact with blood [ 81 ]. Horikawa et al demonstrated that fluorine-incorporated amorphous carbon coatings control the initial thrombotic and inflammatory reactions of biomaterials by suppressing platelet adhesion and activation as well as neutrophil adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…They reported an enhanced water contact angle of DLC by increasing the doping concentration of fluorine, reaching as high as 94 , considerably changed from the original contact angle of 70 (Yoshimoto et al, 2012). Here again, the element doping could effectively change the wettability.…”
Section: Wettability and Other Properties For The Industrial Applicatmentioning
confidence: 95%